2020
DOI: 10.1111/jcpp.13326
|View full text |Cite
|
Sign up to set email alerts
|

Bedtime social media use, sleep, and affective wellbeing in young adults: an experience sampling study

Abstract: Background: Findings from primarily cross-sectional studies have linked more extensive social media use to poorer sleep and affective wellbeing among adolescents and young adults. This study examined bedtime social media use, sleep, and affective wellbeing, using an experience sampling methodology with the aim of establishing a day-today temporal link between the variables. The study hypothesized a positive association between increased bedtime social media use and lower affective wellbeing the following day, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 51 publications
3
47
0
Order By: Relevance
“…Surprisingly, there were no within‐person effects of individual fluctuations in social media use or physical activity compared to a person's usual amount on daily sleep outcomes over this short‐term period, which is consistent with some prior studies (Das‐Friebel et al, 2020 ; Youngstedt et al, 2003 ). However, our findings indicate that girls who use more social media and engage in less physical activity on average report going to sleep later than their peers, and those with higher levels of video chatting have shorter sleep duration.…”
Section: Discussionsupporting
confidence: 90%
“…Surprisingly, there were no within‐person effects of individual fluctuations in social media use or physical activity compared to a person's usual amount on daily sleep outcomes over this short‐term period, which is consistent with some prior studies (Das‐Friebel et al, 2020 ; Youngstedt et al, 2003 ). However, our findings indicate that girls who use more social media and engage in less physical activity on average report going to sleep later than their peers, and those with higher levels of video chatting have shorter sleep duration.…”
Section: Discussionsupporting
confidence: 90%
“…For example, in a 3-year longitudinal study, Tavernier & Willoughby ( 41 ) found that sleep problems predicted more social media use and TV/computer use, and not vice versa. Another study used experience sampling and found that bedtime social media use did not predict poorer sleep the same night ( 42 ). These studies hint that screen use may be a way of coping with sleep problems, rather than causing sleep problems.…”
Section: Discussionmentioning
confidence: 99%
“…Of those, 104 (93.69%) had actigraphy data available. The dataset has been used in other studies (Das-Friebel et al, 2020) but it has not been used for the present purpose.…”
Section: Methodsmentioning
confidence: 99%